Unraveling anesthetic challenges of a patient with dilated cardiomyopathy posted for lower limb amputation surgery -A case report - Ahlawat, Madhu; Asha (UNUSA Press, 2024)
This case report details the anesthetic management of a 64-year-old male with dilated cardiomyopathy (DCM) and a significantly reduced ejection fraction, undergoing lower limb amputation for peripheral arterial disease. Managing anesthesia in such patients poses considerable challenges due to the complexities associated with congestive heart failure. The successful administration of general anesthesia in this case can be attributed to a rigorous preoperative assessment and a meticulously devised anesthetic plan. The systematic approach included careful monitoring, fluid management, and the use of specific anesthetic agents that minimize cardiovascular stress, thereby ensuring an uneventful anesthetic course. This report emphasizes the importance of strategic planning and expert execution in the anesthesia management of patients with severe cardiomyopathy undergoing major surgical procedures.